Clinical outcome of congenital adrenal hyperplasia (CAH) one year following diagnosis: a UK wide study. (4th April 2011) - Knowles, R L; Oerton, J M; Khalid, J M; Hindmarsh, P; Kelnar, C; Dezateux, C
Abstract : Background: Congenital Adrenal Hyperplasia (CAH) is caused by recessively inherited enzyme deficiencies in cortisol production and affects an estimated one child in every 17 000 born in the UK. Children may present with life-threatening adrenal or salt wasting crisis, virilised female genitalia, accelerated growth or precocious puberty. However, detailed information on the short term clinical outcome of CAH is lacking. Aim: To report the spectrum of short-term clinical outcomes at 1 year following diagnosis for children with CAH diagnosed before age 16 years in the UK. Methods: Active surveillance through the British Paediatric Surveillance Unit for 25 months from August 2007 of newly diagnosed CAH in any child <16 years based on clinical features of CAH and elevated 17-hydroxyprogesterone. Short-term outcomes were ascertained by questionnaires to clinicians 1 year following diagnosis. Results: Over a 25 month period, 144 children (62 (43%) chromosomal males) were newly diagnosed with CAH. One child died and 136 (95%) survivors were followed-up 1 year later. Of these, 57 (42%) were boys (chromosomal males) and 125 (92%) had 21-hydroxylase deficiency. Most children (n=131; 96%) were receiving glucocorticoid replacement therapy and over one quarter were also taking mineralocorticoids (n=37). In the first year since diagnosis, 14% of children (19 children; 10 boys) had experienced up to five adrenal crises requiring hospitalisation. 33 children (59% of 56 children diagnosed after age 1 year) demonstrated advanced bone age (median age 7 years; IQR 5–10 years). All children were being raised according to chromosomal sex, with the exception of one boy and two girls who were not. 14 (18%) of girls had undergone genital surgery (median age 1.5 (IQR 1–6.5) years). Conclusions: These findings suggest that serious chronic effects, such as accelerated growth and virilisation, represent an important burden for children living with CAH. Furthermore, children with CAH are at continuing risk of adrenal crises despite active management with replacement therapy suggesting the need for frequent monitoring and accessible support services for families.